¿Cómo hacer la revolución? Los anarquistas y la crítica de la violencia insurreccional - Óscar Freán Hernández (Cahiers de Civilisation Espagnole Contemporaine)
In the thirties of the twentieth century, the Spanish anarchists considered the social revolution as a next and feasible possibility. The crisis of capitalism and the difficulties of the Republican regime reinforced the conviction of this dream of a libertarian Communist society. However, the way of making the revolution created a series of discrepancies inside the anarchist movement. The purpose of this article is to analyse one of these differences, in particular, the use of insurrectionary violence in the framework of a strategy of immediate revolution.